Penyuluhan Pendirian Koperasi Moderasi Beragama Di Desa Kutorojo Kecamatan Kajen Kabupaten Pekalongan - Akhmad Dalil Rohman; Muhammad Harits; Susi Susi; Maulana Ichsan; Esa Fitrotul Maulidiyyah; Inul Inul; Rudi Riyanto; Eva Novitasari; M. Syukron Ni’am; Muhammad Rifa’i Subhi (Pakis Journal Institute, 2024)
This community service project focuses on organizing workshops to establish moderate religious cooperatives in Kutorojo Village, Kajen District, Pekalongan Regency. The significance of this topic lies in addressing the economic challenges faced by the community while promoting religious moderation and social cohesion. The objective is to empower the community economically through the establishment of cooperatives while fostering interfaith understanding and cooperation. The methodological approach involves collaborative efforts between university students, local community members, and government agencies to organize and deliver informative sessions on cooperative formation, legal foundations, and principles. Additionally, discussions and interactive sessions are conducted to encourage active participation and address any concerns or questions. The results indicate a high level of community engagement and enthusiasm towards establishing cooperatives, as well as an improved understanding of the significance of moderation in religious discourse. The workshops serve as a stepping stone towards achieving economic empowerment and social harmony within Kutorojo Village, serving as a potential model for similar initiatives in other communities.